Clinical presentation and outcome in cats with aural squamous cell carcinoma: a review of 25 cases (2010–2021). Issue 10 (October 2022) - McGrath, Alysha M; Chen, Carolyn L; Abrams, Brittany; Hixon, Leah; Grimes, Janet A; Viani, Emily; McLoughlin, Mary A; Tremolada, Giovanni; Lapsley, Janis; Selmic, Laura E
Case series summary: Ear canal neoplasia is uncommon in cats. Ceruminous gland adenocarcinoma is the most frequently reported malignant neoplasm of the feline ear canal, and squamous cell carcinoma (SCC) is the most common malignant neoplasm diagnosed in the feline middle ear. However, limited information exists on the outcome of cats diagnosed with SCC of the ear canal, middle or inner ear. Therefore, the objective of this study was to describe the outcome of cats diagnosed with SCC affecting these locations. Medical records were reviewed at multiple institutions to identify cats with a definitive diagnosis of SCC. Twenty-five cats were identified. Eleven cats were treated with surgery, eight with medical management, two with coarse fractionated radiation therapy, two with a combination of coarse fractionated radiation therapy and chemotherapy, one with a combination of surgery and coarse fractionated radiation therapy, one cat with systemic chemotherapy and one cat received no treatment following diagnosis. The median survival time of cats treated with surgery was 168 days vs 85 days ( P = 0.28) for those treated palliatively with either medical management, radiation therapy, chemotherapy, or a combination of radiation therapy and chemotherapy. Relevance and novel information: This case series documented that SCC of the ear canal, middle and/or internal ear is a locally aggressive tumor that carries an overall poor prognosis. The median survival time for cats treated with surgery was longer than that with any other modality, but this difference was not statistically significant.